Meaning of Life for Autoimmune Survivors during the Pandemic - Subhan Ajrin Sudirman; Masyhuri Masyhuri; Faisal Adnan Reza; Dimas Prastia Putra P (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The Covid-19 pandemic has changed all aspects of life. This phenomenon has caused changes in various aspects of life. It not only affects physical health but also affects human psychological health. Vaccination development continues to be monitored by the government, but there are some people who cannot receive vaccination, such as those with autoimmune diseases. Autoimmune disease is an immune response that causes damage to the body's own tissue and disrupts the body's physiological functions. The coronavirus virus causes the immune system to start producing antibodies that attack the body's own tissue. On the other hand, the symptoms of the coronavirus that still exist, seen in patients who have recovered, also remain a threat to those who have already suffered from autoimmune diseases. The study participants consisted of two 23- year-old women who had had autoimmune diseases for 11 years and a 25-year-old woman who had had autoimmune diseases for 14 years. Data collection was done through interviews and observations. The results showed that the process of achieving meaning in life through sincerity, gratitude, commitment, religious assessment, and social assessment. In addition, the underlying aspects of achieving meaning in life were views on autoimmune diseases, experiences with autoimmune diseases, social support, stress coping, and religious values.